Factors associated with human tolerance of snakes in the southeastern United States - Vaughn, Audrey K.; Larson, Lincoln R.; Peterson, M. Nils; Pacifici, Lara B. (Frontiers in Conservation Science, 2022)
Conservation of snakes is influenced by humans’ beliefs, attitudes, and behaviors toward these often-maligned animals. We investigated public attitudes toward snakes through an online survey of undergraduate students (n = 743) at a large public university in a southeastern U.S. state. We used behavioral intent (i.e., how a person would react if they encountered a snake) to assess tolerance of different snake species. We also examined various predictors of tolerance including demographic attributes and variety of cognitive (e.g., knowledge, value orientations) and affective (e.g., emotions) social-psychological variables. Tolerance of snakes varied based on whether the snake was venomous or non-venomous: about 36% of students said they were likely to kill venomous snakes they encountered, compared with 9% who said they would kill non-venomous snakes and 21% of students who said they would kill snakes whose identity was uncertain. However, most students (54%) could not distinguish between venomous and non-venomous species. Value orientations and emotions were strong predictors of tolerance for snakes, suggesting snake outreach and management strategies should account for both cognitive and affective antecedents of behavior.